Analyzing the Implications of Public Debt on Budget Implementation in Sub-Saharan Africa: A Public Choice Theory Perspective - (:unkn) unknown (My University, 2025)
This study investigated the implications of public debt on budget implementation in Sub-Saharan African countries. Specifically, it examined how the allocation of resources towards servicing public debt affects budget implementation, it assessed the extent to which budget deficits drive borrowing and their impact on the implementation of budgetary plans as well as analyzed how fluctuations in interest rates influence the sustainability of public debt spanning from 2012 to 2021. The population consisted of sixteen countries randomly selected from East, West, Central, and South regions of Sub-Saharan Africa based on GDP size as of December 2021. This study made use of secondary data through ex post facto research design and data were sources through World Bank indicator, utilizing panel data analysis techniques, including descriptive statistics. The findings of this study reveal the significant positive relationship between actual debt servicing (ADS) and government final consumption expenditure (GFE) underscores the effective allocation of resources towards servicing public debt directly influences budget implementation. Secondly, while interest rates (INTR) and domestic debt (DDT) do not exhibit significant impacts on GFE, the mixed results regarding foreign debt (FDT) highlight the complex dynamics of borrowing patterns and their influence on budgetary plans. The significant impact of the exchange rate (EXTR) on GFE emphasizes the importance of external factors in shaping budget implementation, particularly in Sub-Saharan African countries where exchange rate fluctuations can significantly affect debt sustainability and fiscal stability. These findings underscore the multifaceted nature of budget implementation and highlight the interconnectedness between resource allocation for servicing public debt, borrowing patterns, and external factors such as interest rates and exchange rates in Sub-Saharan African countries.
Keywords: African Research